2014
DOI: 10.4236/ajps.2014.520323
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Arbuscular Mycorrhizal Fungi and Their Partner Bacteria on the Growth of Sesame Plants and the Concentration of Sesamin in the Seeds

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Although some Pseudomonas species are generally recognized to release the synthesis of plant growth-promoting substances and production of antibiotics [11], in the present study, the effect of the Pseudomonas sp. strain 13134 alone on root morphology was more pronounced under the soil condition rather than under the substrate condition (Figure 1).…”
Section: Root Morphology and Phosphorus Uptakementioning
confidence: 84%
See 2 more Smart Citations
“…Although some Pseudomonas species are generally recognized to release the synthesis of plant growth-promoting substances and production of antibiotics [11], in the present study, the effect of the Pseudomonas sp. strain 13134 alone on root morphology was more pronounced under the soil condition rather than under the substrate condition (Figure 1).…”
Section: Root Morphology and Phosphorus Uptakementioning
confidence: 84%
“…Another study found that the AM fungi colonization rate was increased from 39.2% ± 5.8% to 66.4% ± 4.4% by the cooperation of partner bacteria [11]. The rate of sesame root colonization in Glomeas clarum IK97 + Pseudomonas sp.-inoculated plants (66.4% ± 4.4%) was higher than that in G. clarum IK97-alone-inoculated plants (39.2% ± 5.8%) [11]. Some Pseudomonas sp.…”
Section: Colonization Of Am Fungi Ratementioning
confidence: 98%
See 1 more Smart Citation
“…FW, fresh weight; DW, dry weight. symbiosis establishment, 5 g of mycorrhizal inoculant (Horii and Ishii, 2014) according to company recipe and a modified method of Al-Karaki and Clark (1999) was added into each planting hole. Seeds were placed on the top of the inoculant (Al- Karaki and Clark, 1999).…”
Section: Amf Inoculationmentioning
confidence: 99%
“…Arbuscular mycorrhizal fungi (AMF) have interactions with a broad range of plants in nature Read, 2008, as cited in Wehner et al, 2010). AMF inoculation of crops due to an increase in yield and growth (Hamel and Plenchette, 2007, as cited in Horii and Ishii, 2014). Promoting tolerance against water deficit and growth has been observed in papaya plants associated with AMF (Cruz et al, 2000, as cited in Horii and Ishii, 2014).…”
Section: Introductionmentioning
confidence: 99%